PENGARUH KECERDASAN EMOSIONAL TERHADAP PRESTASI DAN SIKAP BELAJAR MATEMATIKA SISWA DALAM PEMBELAJARAN EKSPOSITORI - Yashinta, Acintya Pramudita; Ariyanti, Gregoria (Educatio Vitae, 2015)
The purpose of this research is to know: (1)Whether or not there was some influence of emotional intelligence to students’ achievement in Mathematics. (2)  Whether or not there was some influence of emotional intelligence students’ attitude in Mathematics. This research is a quantitative Pre-Experiment Design. It was implemented to the second semester students of the academic year 2013/2014 of St. Thomas Aquino Senior High School Tulungagung with the class X as population. While, the sample of this research was the student of the class XE with Expository Learning. To obtain the sample, this research applied cluster random sampling technique. The techniques of data collection used were test with achievement test in Mathematics instrument and non test techniques with Emotional Intelligence questionnaire and students’ attitude in Mathematics questionnaire instruments. The achievement test was used to know the students’ achievement in Mathematics, while Emotional intelligence questionnaire was used to know the level of the students’ Emotional Intelligence, and students’ attitude in Mathematics questionnaire was used to know students’ attitude in Mathematics. The instruments were validated before trial. The result of research showed that (1) there was no influence of Emotional Intelligence to students’ achievement in Mathematics and (2) there was influence of Emotional Intelligence to students’ attitude in Mathematics.